The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/fermentation9060533
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Cocoa (Theobroma cacao L.) Pulp by Laetiporus persicinus Yields a Novel Beverage with Tropical Aroma

Victoria Klis,
Eva Pühn,
Jeanny Jaline Jerschow
et al.

Abstract: Cocoa pulp represents an interesting by-product of cocoa production, with an appealing flavor. We developed a non-alcoholic beverage via the submerged fermentation of 10% pasteurized cocoa pulp in water with Laetiporus persicinus for 48 h; the product was characterized by tropical fruity notes such as coconut, mango, passion fruit and peach. The overall acceptance of the beverage compared to the non-fermented medium, as rated by a panel, increased from 2.9 to 3.7 (out of 5.0 points) for odor and from 2.1 to 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Regarding acids, one of the predominant compounds in SC was acetic acid (Table S4), which was similar to that reported by Chagas et al [99] and Sandoval-Lozano et al [100], which began to increase dramatically between 48 and 72 h of fermentation, a period in which it is associated with a conversion of ethanol to acetic acid, where the yeast S. cerevisiae contributes to the oxidation of alcohol [22,99,100]. A higher content of linalool could be observed in SC compared to SF, as reported by Assi-Clair et al [22]; our study showed high concentrations after 48 h of fermentation similar to Klis et al [101]; finally, a shorter presence of isobutyl acetate (48 h) was detected in SC, presenting floral, fruity and banana notes [102], as detected in the same type of fermentation in the study of Assi-Clair et al [22]. S3).…”
Section: Characterization Of the Profile Of Volatile Compounds (Vcs) ...supporting
confidence: 88%
“…Regarding acids, one of the predominant compounds in SC was acetic acid (Table S4), which was similar to that reported by Chagas et al [99] and Sandoval-Lozano et al [100], which began to increase dramatically between 48 and 72 h of fermentation, a period in which it is associated with a conversion of ethanol to acetic acid, where the yeast S. cerevisiae contributes to the oxidation of alcohol [22,99,100]. A higher content of linalool could be observed in SC compared to SF, as reported by Assi-Clair et al [22]; our study showed high concentrations after 48 h of fermentation similar to Klis et al [101]; finally, a shorter presence of isobutyl acetate (48 h) was detected in SC, presenting floral, fruity and banana notes [102], as detected in the same type of fermentation in the study of Assi-Clair et al [22]. S3).…”
Section: Characterization Of the Profile Of Volatile Compounds (Vcs) ...supporting
confidence: 88%
“…The application of mycelium from side stream fermentations can be performed in different ways: the processing of the mycelium–substrate complex as a whole, the mycelium separated from the substrate, the protein extracted from the mycelium, and the protein secreted by the fungus (Scholtmeijer et al., 2023 ). Furthermore, the fermentation of higher mushrooms offers possibilities to improve the organoleptic properties of agricultural side‐streams, such as by‐products from the cocoa industry (Klis et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pleasant flavour of cocoa pulp makes it highly attractive for the international food sector, especially for the development of beverages ( Klis et al, 2023 ). Only a few studies focused on the aroma composition of cocoa pulp.…”
Section: Introductionmentioning
confidence: 99%